Platelet‐derived lipids promote insulin secretion of pancreatic β cells - Till Karwen; Katarzyna Kolczynska‐Matysiak; Carina Gross; Mona C Löffler; Mike Friedrich; Angel Loza‐Valdes; Werner Schmitz; Magdalena Wit; Filip Dziaczkowski; Andrei Belykh; Jonathan Trujillo‐Viera; Rabih El‐Merahbi; et al. (EMBO Molecular Medicine)
Abstract Hyperreactive platelets are commonly observed in diabetic patients indicating a potential link between glucose homeostasis and platelet reactivity. This raises the possibility that platelets may play a role in the regulation of metabolism. Pancreatic β cells are the central regulators of systemic glucose homeostasis. Here, we show that factor(s) derived from β cells stimulate platelet activity and platelets selectively localize to the vascular endothelium of pancreatic islets. Both depletion of platelets and ablation of major platelet adhesion or activation pathways consistently resulted in impaired glucose tolerance and decreased circulating insulin levels. Furthermore, we found platelet‐derived lipid classes to promote insulin secretion and identified 20‐Hydroxyeicosatetraenoic acid (20‐HETE) as the main factor promoting β cells function. Finally, we demonstrate that the levels of platelet‐derived 20‐HETE decline with age and that this parallels with reduced impact of platelets on β cell function. Our findings identify an unexpected function of platelets in the regulation of insulin secretion and glucose metabolism, which promotes metabolic fitness in young individuals.